POLA KOMUNIKASI ORANGTUA DAN ANAK DALAM MENGAWASI ANAK MENGGUNAKAN GADGET - Ajeng Novita Handayani; Yanuar Luqman (Interaksi Online, 2022)
Today's gadgets have become a necessity for everyone from children to adults. The use of gadgets certainly has positive and negative impacts for users and it depends on their use. Parents now cannot completely prohibit their children from using smartphones because their obligations as students during the covid-19 pandemic have been changed to online and they have to stare at the screen from the morning. The role of parents in this situation is very important. Parents must be a companion, mentor and also a 'friend' to relieve boredom in children who have to stay at home. If the parents are busy, the child may be looking for entertainment through the device. The use of gadgets that are not accompanied by parents and not controlled, children will be free to access anything and will have a negative impact on children's development in the future. The purpose of this study was to describe and determine the process of interpersonal communication between parents and children who have been facilitated by gadgets and to find out the assistance and policies provided by parents to their children regarding the use of gadgets. The theory used is Family Communication Pattern and Parental Mediation Theory. The research method is using a qualitative approach to phenomenology. The results showed that the supervision of the use of gadgets in children in the family was carried out through dialogue/communication and mediation. This is done to space out the negative effects of using gadgets on children. All informants' families were found to use democratic communication patterns. Where parents and children are very open about everything, and children are allowed to express their opinions during discussions or when making decisions. Regulations regarding gadgets are made based on mutual agreement so that there is no compulsion when undergoing it. In terms of mediation, the five informants' parents chose to use limited mediation and some of these regulations were made only in words and some were made in writing, and there was one parent informant who used active mediation. it's more of a chat.